Juridical Analysis of the Comparison of Different Religious Marriage Laws Based on the Adminduk Law Article 35 with SEMA No 2 Years 2023 Concerning Marriage Registration - Lumbantoruan, Sahala; Isnainul, Ok; Adawiyah, Rodiatun (International Journal of Business, Law, and Education, 2024)
Interfaith marriage is an issue that has not been resolved to date. In current practice in Indonesian society, interfaith marriage processions are generally carried out by carrying out the marriage with a religious procession each of which is followed by the prospective husband and wife or in the sense that there are two religious processes being carried out or only carrying out one religious procession or what generally happens is not carrying out religious processions at all so that it does not comply with Article 2 paragraph (1) of the Marriage Law regarding valid marriages. The legal research method used in this research is normative juridical research which is research carried out or aimed only at written regulations with the nature of descriptive analysis research which is a method that functions to describe or provide an overview of the object being studied. The data source used is secondary data with quantitative data analysis. The results of this research are the Hierarchy of Legislation in Indonesia. If it is related to the Civil Admin Law Article 35 with SEMA Number 2 of 2023, the legal force of SEMA has a lower hierarchy than the law. Therefore, it can be concluded that the provisions contained in the Administer Law cannot be changed by SEMA Number 2 of 2023. However, this SEMA still influences the direction for judges not to grant requests for inter-religious marriages.